Lama Waktu Perendaman Larva Ikan Gabus (Channa Striata) Dalam Larutan Hormon Tiroksin Untuk Meningkatkan Pertumbuhan Dan Kelangsungan Hidup - Andre F Pasaribu; Muslim Muslim; Mochamad Syaifudin (Universitas Sriwijaya, 2019)
The thyroxine has been known as a hormone that can increase fish growth especially in the larvae stage. The provision of hormone thyroxine on larvae fish can be conducted through dipping. Determination of dipping time are very important to increase growth. The purposes of this research are determining the optimum dipping time for the growth and survival rate of snakehead larvae. This research was done at Laboratorium Dasar Perikanan, Aquaculture, Faculty of Agriculture, University of Sriwijaya, Indralaya. The method used Competely Randomized Design (RAL) with five treatments and three replicates, with dipping time are 24, 27, 30, 33 and 36 hours. The parameters observed are the absolute length growth, absolute weight growth, survival rate of larvae and water quality (temperature, pH and disolved oxygen). The results showed that the duration of immersion in thyroxine hormone solution in snakehead larvae showed relatively faster growth on treatment (P5) with 36 hours of dipping time. While the regression test result showed the optimal growth of snakehead larvae at the time immersion for 27,92 – 29,49 hours. Thyroxine hormone increased the growth of snakehead larvae but has no statistically significant effect. The length of time of thyroxine hormone 24-36 hours with a dosage of 0.1 mg l-1 did not affect the survival of snakehead larvae. Water quality of maintenance media is still tolerance for supporting the growth and survival of snakehead larvae.